2019
DOI: 10.1108/jfbm-09-2018-0047
|View full text |Cite
|
Sign up to set email alerts
|

The effect of internal controls on financial reporting quality in Iranian family firms

Abstract: Purpose The purpose of this paper is to investigate the relationship between internal controls weakness and financial reporting quality and the effect of family ownership on the mentioned relationship in Iranian listed firms. Design/methodology/approach In this way, the authors included the number of 139 firms from 2013 to 2017, of which 28 were family firms. The hypotheses are analyzed based on panel data and means comparison. Findings The results illustrated that weakness in internal controls has a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 76 publications
3
32
0
11
Order By: Relevance
“…COSO which published the "Internal Control Integrated Framework" which has designed to help businesses establish, assess and enhance their internal control. The COSO framework defines internal control as a process, carried out by the board of directors, the administration and other personnel of an entity, designed to provide "reasonable security" with respect to the achievement of objectives, including the effectiveness and efficiency of the operations, the reliability of financial reports, and the compliance with applicable laws and regulations (Lari Dashtbayaz, Salehi, & Safdel, 2019). The COSO internal control framework consists of five interrelated components as control environment, risk assessment, control activities, information and communication, and monitoring derived from the way in which the administration manages a business (Hazami-Ammar, 2019).…”
Section: Internal Control Effectivenessmentioning
confidence: 99%
“…COSO which published the "Internal Control Integrated Framework" which has designed to help businesses establish, assess and enhance their internal control. The COSO framework defines internal control as a process, carried out by the board of directors, the administration and other personnel of an entity, designed to provide "reasonable security" with respect to the achievement of objectives, including the effectiveness and efficiency of the operations, the reliability of financial reports, and the compliance with applicable laws and regulations (Lari Dashtbayaz, Salehi, & Safdel, 2019). The COSO internal control framework consists of five interrelated components as control environment, risk assessment, control activities, information and communication, and monitoring derived from the way in which the administration manages a business (Hazami-Ammar, 2019).…”
Section: Internal Control Effectivenessmentioning
confidence: 99%
“…Thus, authors conclude that in FFs, the agency's conflicts between family owners and managers are less pronounced and they are not adequately motivated to maximize their personal interests and influence the financial reporting process. On the other hand, in the same stock exchange market (Iran), Lari Dashtbayaz et al (2019) find no relationship between family ownership and FRQ and that the control of equity owners over the firms' operation does not improve the level of internal controls. The supply of higher earnings quality attributable to the alignment effect, however, may be mitigated by the lower demand for higher earnings quality if users of financial statements take it for granted that FFs have stronger corporate governance.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The study [11] investigated the effect of internal controls on financial reporting quality in Iranian family firms. The findings revealed that weakness in internal controls has a significant negative relationship with financial reporting quality.…”
Section: Empirical Reviewmentioning
confidence: 99%